Análisis competitivo de España y los NEM. Cambios en la estructura productiva y efectos de la IED. - Alonso, Fernando; Prada, Álavaro (Papeles del Este, 2007)
This article explores how transformations in the productive structures of Eastern European Countries and Spain have impacted their processes of economic transformation and the opening of their markets to business and international competition, in the context of the challenges and opportunities ushered in by these transformations. Changes have had a major influence on hiring practices in the agricultural sector, the tertiarization of economies and the profound restructuring in the industrial sector, all of which have caused substantial changes in employment, productivity and industrial competition. Foreign investment has been a driving force behind trends in the industrial specialization in most of the New Member States, at times apparently in an altogether capricious fashion, by focusing interest on certain countries and sectors.